Sport during the Boer Wars: An Ordinary Practice? - (:unkn) unknown (My University, 2012)
The Anglo-Boer War (1899-1902) was the pinnacle of a dispute in the troubled relations between two white races in nineteenth century South Africa — the Afrikaner and the British. As imperialist Britain struggled to exert control of South Africa during this period the war, in many respects, represented the start of the decline of the British Empire. Sport however was established at this time as an important part of colonial culture for the British as well as a popular recreation for their opponents — the Republican Afrikaners (or ‘Boers’). Despite the centrality of sport in South Africa, relatively little has been written to date of the significance of sport to both sides during this period as well as during the war itself. This paper will build upon my existing studies in this area to explore the affect the conflict had on the development of sport in South Africa as well as examining the nature and role of sport within both the allied and Boer forces.
Keywords: African Research